Pain management in pediatric age. An update - Di Sarno, Lorenzo; Gatto, Antonio; Korn, David; Pansini, Valeria; Curatola, Antonietta; Ferretti, Serena; Capossela, Lavinia; Graglia, Benedetta; Chiaretti, Antonio (Acta Biomedica Atenei Parmensis, 2023)
Differently from the adult patients, in paediatric age it is more difficult to assess and treat efficaciously the pain and often this symptom is undertreated or not treated. In children, a selection of appropriate pain assessment tools should consider the age, the cognitive level, the presence of eventual disability, the type of pain and the situation in which it is occurring. Improved understanding of developmental neurobiology and paediatric analgesic drug pharmacokinetics should facilitate a better management of childhood pain. The objective of this update is to discuss the current practice and the recent advances in pediatric pain management. Using PubMed and the Cochrane Library we conducted an extensive literature analysis on pediatric pain assessment and commonly used analgesic agents in this kind of patients. According to our results, a multimodal analgesic regimen provides a better pain control and a functional outcome in children. Cooperation and communication among the anaesthesiologist, the surgeon and the paediatrician remains essential for successful anaesthesia and pain management in childhood.